NEWFOUND FREEDOM: A RESILIENT JOURNEY TO BREAKING THE SPELL - Keleş, Aybike (Cocuk ve Genclik Edebiyati Yazarlari Dernegi, 2025)
Ella Enchanted by Gail Carson Levine narrates the tale of a young girl named Ella, who fell under a curse bestowed upon her by a fairy at her birth and her tenacious battle to break the spell. Obedience enchantment compels Ella to blindly comply with the dictates of those around her, thereby depriving her of the ability to exercise her own will and make decisions independently. During the story, Ella goes through a number of tests that force her to decide for herself and shape her own future. However, instead of casting her hope in a prince or depending on magical remedies, she liberates herself from the curse by employing her own resolve and fortitude. In this narrative, the construction of gender roles are reproduced. By digging into Ella’s journey to liberate herself from the restrictions of the curse, the writer skillfully explores the themes of resilience, freedom of choice, and self-discovery. The author challenges some deeply rooted beliefs found in classic fairy tales. She condemns a society that limits women's independence and promotes the idea that marriage is the only way for them to achieve fulfillment. The character's unwavering confidence in her own capabilities and her fierce warrior spirit are the fundamental elements that distinguish this tale from the other fairy tales. Her unwavering will to free herself from the enchantment, without the help of a prince, exemplifies her rejection of societal notions of gender and traditional gender roles for women. Just as Medusa’s laugh serving as a metaphor for the ability to challenge the norms assigned to women, Ella’s act of breaking the curse symbolizes her reclaiming control over her destiny. Through her awakening, the protagonist stepped into a newfound sense of empowerment and redefines her identity on her own terms Her newfound independence enables her to discover inner power, leading her to become the heroine of her own story. By examining the protagonist’s journey into a powerful individual, this research aims to explore how her breaking the curse disrupts the conventional gender roles within the context of fairy tales. This paper also makes a significant contribution to redefine traditional gender roles in literature society by juxtaposing the experiences of the main character with those of the traditional Cinderella figure. By interweaving elements from classic fairy tales into Ella's narrative, this search paper highlights the development of new storytelling methods and long lasting role of fairy tales on the formation of cultural consciousness.
Keywords: Literary Theory; Resilience; Curse; Awakening; Conventional; Gender; Azim; Lanet; Uyanış; Geleneksel; Cinsiyet; Edebi Teori